Globalisation and liberalisation of Malaysian higher education / Fadli Fizari Abu Hassan Asari, Suriyani Muhamad and Puteri Zarina Megat Khalid - Abu Hassan Asar, Fadli Fizari; Muhamad, Suriyani; Megat Khalid, Puteri Zarina (Universiti Teknologi Mara Cawangan Pulau Pinang, 2017)
Tertiary enrolment of international students is to quadruple from 1.8 million in 2000 to 7.2 million in 2025. The key factors are liberalisation and globalisation of higher education. In Malaysia, these processes were initiated in the 1980’s. Starting as an Import-Substitution Industrialisation (ISI), higher education had transformed into an Export-Oriented Industrialisation (EOI) in the 1990’s, followed by another expansionary stage in the 2010’s. These initiatives reflect Malaysian commitment in enrolling more international students into the local institutions. In another current development, Malaysia has been ranked as one of the leading nations in supporting the internationalisation of higher education, together with Germany. Thus, realising the positive impact of higher education on Malaysian economy, this sector has been identified as one of the National Key Economic Areas (NKEAs) which is expected to generate an additional income of RM2.8 billion by the year 2020.